Development of Digital Interactive Module “E-MOSI” (Elektronik Modul Puisi) for Grade IV Students of Elementary School of Kemala Bhayangkari 02 - Lily Nafilatul Maulidiana; Andarini Permata Cahyaningtyas; Yulina Ismiyanti (Universitas Pendidikan Indonesia Kampus Serang, 2021)
This study aims to develop electronic module teaching materials for fourth-grade poetry and determine their feasibility and practicality. This research is motivated by the difficulty of understanding Indonesian subjects, especially poetry materials, and the lack of alternative teaching materials. The novelty of this teaching material is in the form of modules that can be accessed utilizing gadgets and laptops, as well as the completeness of materials supported by audio and video learning. This type of research is development research, using the research and development method, consisting of ten development steps (potentials and problems, collecting data, product design, design validation, design revision, product trial, product revision, usage trial, product revision, and mass production. Based on these ten steps, the development of the digital interactive module